PERFORAMCE OF GUAVA GENOTYPE TO QUALITATIVE AND YIELD ATTRIBUTES - PRADIPKUMAR H. ULEMALE; TUKARAM B. TAMBE (The Bioscan, 2015)
The present investigation was carried out on nine genotypes of guava,in randomized block design with three replications of each genotype. The results were obtained for the quality and biochemical characters. The most of the genotypes were observed whitish green and whitish yellow colour of fruit. Whereas, cuneate and oblong shaped fruit was noted in most of the genotypes.The most of the genotypes viz., GWS5, GWS6, GWS7, GWS8 and L-49 had white pulp colour with hard seed. Light pink colour of pulp with intermediate seed hardness was observed in genotypes GRS1, GRS2 and GRS3, whereas, it was medium dark pink colour of pulp with soft seed in GRS4 genotype.The genotype L-49 recorded the highest pulp weight (206.02g).The genotype GRS4 had significantly, the lowest number seed and weight of seeds per fruit (194.33) and (1.91g). The genotype L-49 was recorded the highest fruit weight (214.03 g).The highest pulp content (96.55%), pulp: seed ratio (66.42), number of fruit per tree (406.44) and fruit yield (52.9 kg/tree and 21.15 Mt/ha) was observed in genotype GRS4.